2012
DOI: 10.1111/j.1747-4949.2012.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Burden in Adults in Armenia

Abstract: We investigated around 100 patients for one-year and then registered the information about the possible etiology of the stroke, type of disease, treatment, localization of the clot, age, as well as gender distribution of stroke patients' population. This general overview of risk factors, ways of treatment, diagnostics, care and monitoring of the stroke patients in Armenia might serve as a cornerstone work for further highlighting of new avenues for stroke treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Crude incidence from stroke according to (a) the proportion of the population aged ≥65 years ( Y = 8.849* X + 72.31, P < 0.0001), and (b) the midyear that the study was conducted ( Y = 1.265* X – 2353, P = 0.37). These are for all countries that have reported crude incidence, and for which population estimates were reported to the World Health Organization (5,6,10,11,14,15,17,19,23,24,2628,32,3862). …”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Crude incidence from stroke according to (a) the proportion of the population aged ≥65 years ( Y = 8.849* X + 72.31, P < 0.0001), and (b) the midyear that the study was conducted ( Y = 1.265* X – 2353, P = 0.37). These are for all countries that have reported crude incidence, and for which population estimates were reported to the World Health Organization (5,6,10,11,14,15,17,19,23,24,2628,32,3862). …”
Section: Incidencementioning
confidence: 99%
“…In 18 of these reviews, total stroke incidence and separate rates for men and women were reported (5,6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In 10 of these reviews, only total stroke incidence was reported for the country (7,10,(27)(28)(29)(30)(31)(32)(33)(34), whereas in four reviews, only gender-specific incidence rates were provided (35)(36)(37)(38).…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Among other efforts, Armenia has modernized its primary care network, enforced tobacco control, and instituted state of the art cardiac and stroke care. [5][6][7][8] Like many middle-income countries, Armenia had challenges controlling the spread of coronavirus disease 2019 (COVID-19). There was a lack of personal protective equipment, a lack of ventilators, and a lack of testing.…”
mentioning
confidence: 99%